2021
DOI: 10.3233/thc-202659
|View full text |Cite
|
Sign up to set email alerts
|

Improved NLMS-based adaptive denoising method for ECG signals

Abstract: BACKGROUND: Traditional least mean square algorithm (LMS) tends to converge faster and thus the larger the steady-state error of the algorithm. OBJECTIVE: In order to solve this issue, an improved adaptive normalized least mean square (NLMS) ECG signal denoising algorithm is proposed through utilizing the NLMS and the least mean square algorithm with added momentum term (MLMS). METHODS: The algorithm firstly performs LMS adaptive filtering on the original ECG signal. Then, the algorithm uses the relative error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…The average specificity of the experimental group (98%) was higher than that of the control group (84%), with significant difference ( P < 0.05). The above data showed that the efficiency of ultrasonic elastography combined with HPV detection in the diagnosis of cervical intraepithelial neoplasia with intelligent denoising algorithm was higher than that without algorithm optimization, which was consistent with the research results of Wang et al [ 28 ]. Then, the ultrasonic elastography of intelligent denoising algorithm was analyzed, and two experimental subjects were randomly selected.…”
Section: Discussionsupporting
confidence: 91%
“…The average specificity of the experimental group (98%) was higher than that of the control group (84%), with significant difference ( P < 0.05). The above data showed that the efficiency of ultrasonic elastography combined with HPV detection in the diagnosis of cervical intraepithelial neoplasia with intelligent denoising algorithm was higher than that without algorithm optimization, which was consistent with the research results of Wang et al [ 28 ]. Then, the ultrasonic elastography of intelligent denoising algorithm was analyzed, and two experimental subjects were randomly selected.…”
Section: Discussionsupporting
confidence: 91%
“…The adaptive filtering algorithm used in this work was the normalized least mean squares (NLMS) [ 19 ]. In the application process, the step factor was optimized by inputting the square Euclidean norm of a ( n ) into the adaptive filter, then the step factor can be defined as follows: …”
Section: Methodsmentioning
confidence: 99%
“…The performance of LMS is mainly affected by three factors: step size, input vector u ( n ), and estimation error. [ 29 ] The advantages of the LMS algorithm are as follows: simplicity and ease of implementation, low complexity, and the suppressed side‐lobe effect. Disadvantages include a slow convergence rate, poor tracking performance, and the stability of the system decreasing with the increase of the filter order (step size parameter).…”
Section: Methodsmentioning
confidence: 99%
“…RLS is a transverse filter with length M and coefficient w(n). [28,29] At each time step, the coefficients are updated through the adaptive control unit using the input vector u(n). The prior estimation error represents the deviation between the expected output and the actual output.…”
Section: Adaptive Recursive Least Squares Denoising Approachmentioning
confidence: 99%